The Role of Flexible Work Arrangement, Job Embeddedness, and Work-Life Balance in Reducing Turnover Intention: Study on Millennials and Generation Z Employees - Rosita, Ferriyal; Noermijati, Noermijati; Setiawan, Margono; Susilowati, Christin (Journal of The Community Development in Asia, 2024)
Millennials and Generation Z, as the largest demographics entering the workforce, were anticipated to drive national progress. However, despite their significant numbers, many of them are experiencing high turnover rates. This study investigates the role of flexible work arrangements, job embeddedness, and work-life balance in suppressing turnover intention among millennials and Generation Z in multi-finance companies at Jakarta headquarters. This research is quantitative research with non-probability sampling. The questionnaire was distributed to 280 respondents. The data analysis technique uses Partial Least Square (PLS) analysis tools. The results indicate that (1) flexible work arrangement has a significant negative impact on turnover intention; (2) flexible work arrangement has a significant positive impact on job embeddedness and work-life balance; and (3) flexible work arrangement has a significant negative impact on turnover intention which is partially intervened by job embeddedness and work-life balance. It is suggested for multi-finance companies to optimize flexible work arrangement practices by implementing work-life balance and job embeddedness to reduce turnover intention among millennials and Generation Z